Legal Protection of Indonesian Migrant Woekers Reviewed According to Law Number 18 of 2017 Concerning the Protection of Indonesian Migrant Workers - Delia Mutiara Rahmah Sri Ma’ruf (Rechtsnormen: Journal of Law, 2024)
Background. The government has issued laws and regulations regarding the protection of Indonesian Migrant Workers. However, the large number of Indonesian Migrant Workers abroad has led to many problems faced by Migrant Workers. Purpose. In this thesis, the problem is how the protection of Indonesian Migrant Workers according to Law Number 18 of 2017 and how the government's efforts in providing legal protection for Indonesian Migrant Workers. Method. In conducting this research the author uses library research and field research, which is in the form of data collection and is extracted based on literatulism such as, books, print media, electronic media, internet media and interviews, the data is obtained from legal materials related to the Protection of Indonesian Migrants. Results. The results and conclusions of the research show that the Protection of Indonesian Migrant Workers based on Law Number 18 of 2017, the protection of Indonesian Migrant Workers is all efforts to protect the interests of prospective Indonesian Migrant Workers and / or Indonesian Migrant Workers and their families in realizing the guaranteed fulfillment of their rights in legal, economic and social aspects Conclusion. The government's efforts so far can be seen in the form of laws and regulations issued in response to the needs of Indonesian Migrant Workers. Indicators of the condition of protection of Indonesian Migrant Workers can at least be seen from three aspects, namely pre-placement, placement and post-placement